Effect of Iodide-Based Organic Salts and Ionic Liquid Additives in Dye-Sensitized Solar Cell Performance - Sarrato, João (2022)
Funding Information: This work was performed under the project PTDC/QUI-QOR/7450/2020 “Organic Redox Mediators For Energy Conversion” through Fundação para a Ciência e a Tecnologia I. P.-FCT. Additional support includes the Associate Laboratory for Green Chemistry–LAQV, financed by national funds from FCT/MCTES (UIDB/50006/2020 and UIDP/50006/2020). FCT/MCTES is also acknowledged for the National NMR Facility (RECI/BBB-BQB/0230/2012 and RECI/BBB-BEP/0124/2012,) and Ph.D. grants 2020.09047.BD (J.S.), PD/BD/135087/2017 (A.L.P.) and PD/BD/145324/2019/ (G.M.). Publisher Copyright: © 2022 by the authors.